Reforma del art. 18 numeral 22 de la ley notarial, que en el trámite de divorcio por mutuo consentimiento se incorpore como requisito que la cónyuge al momento de presentar al petitorio exprese bajo juramento de no encontrarse en estado de gravidez . - Ramírez Vidal, Luz Elizabeth (2014)
Divorce in our country is still in the courts by the rules contained in the Civil Code either by mutual agreement or causal, or is the notarial procedure, followed by the Notarial Act, in the case of mutual agreement and provided when spouses have no minor children or under his authority. Thus, in Article 18 paragraph 22 of the Notarial Act authorizes notaries divorce by mutual consent, for which the spouses expressed in the petition under oath will dissolve their marriage bond, for which they indicate that have no minor children or who are under dependency. But nothing particularly indicated Cunado the woman is during pregnancy, for which it should be noted that, under oath in order to enable women to hide her pregnant and this goes against family protection guaranteed by the Constitution and the Law. Being a divorce by mutual consent is an act of voluntary jurisdiction, it is exercised in matters which by their nature or because of the state of things, resolve without contradiction, that is why the law has granted the power of proceed to divorce by mutual consent before the Notary, being an act of will of the parties to terminate the marriage. You need be specified in the Notary Act, the status of pregnancy that may be the spouse requesting the termination of marriage, because it can happen that you hide for any reason, and this may affect the rights of spouses and therefore the children and adolescents to be victims of their parents' separation. For it is to be noted that if the spouse is in a state of pregnancy, is in distress the child to be born, because children will financially dependent on their parents, so it should not be granted the dissolution of the marriage, but shall be this process according to the rules of the Civil Code, that before one of the judges of the civil judicial units.